The Role of Local Cuisines in Creative Tourism Process: A Case Study of Lao Khrang Ethnic Group in Chai Nat Province - Yanapa Booparkob ญาณภา บุญประกอบ; Jakawan Wongmanee จักรวาล วงศ์มณี; เขตเจนการ สิริพร; แสวงดี โยธิน (Dusit Thani College Journal, 2018)
This paper aims to 1) study local food wisdom and 2) develop creative tourism activities for community tourism. The paper use a qualitative method with the triangulation approach to analyze. The primary data were obtained from all involved stakeholders, such as local people, leader, authorities, and related government agencies, by conducting observation participation, in-depth interview, focus group discussion, and group interview to identify local food wisdom and current tourism activities within the case study area. The documentary research was also conducted from different sources and related empirical studies. The findings indicate that Lao Khrang ethnic group in Chai Nat has been preserving its symbolic foods, such as Pla ra (Fermented fish), Pla-Dook Tom Pla ra (Catfish in fermented fish soup), Jaew Kai (Minced chicken spicy sauce), and Kanom Dak Kao Pod (Steamed sweet corn wrapped with banana leaf or corn leaf). This study has emphasized on the use of symbolic foods through creative tourism process in relation to conservation, rehabilitation, adaptation, and creation, in creating new creative tourist activities for community tourism promotion. Finally, the study has proposed the possible cooking activities for Lao Khrang ethnic group in Chai Nat based on the creative tourism concept.